Hypercyclic operators with an in¯nite dimensional closed subspace of periodic points - Grivaux, Sophie (Revista Matemática Complutense, 2003)
Let X be an infinite dimensional separable Banach space. There exists a hypercyclic operator on X which is equal to the identity operator on an infinite dimensional closed subspace of X.